ED Brake Priority of Emergence Brake and Its Application to LIM Vehicle - ZHENG Wo-qi (机车电传动)
According to the abrupt slope of LIM line and the ED brake of LIM vehicle not depending on adhesion, ED brake priority of emergence brake was applied to Guangzhou LIM vehicle. The design and test of the scheme were introduced, which could reduce the vehicle brake distance effectively of rainy condition and ensure operation safety.